(untitled) (Medico Legal Update, 2021)
Female workers are a vulnerable group in Indonesia because in addition to working to help their husbands earn a living, they also still have to be responsible for domestic affairs. This study aimed to analyze the effect of the level of education on the incidence of LBW in female workers in Indonesia. The analysis uses the 2017 Indonesian Demographic and Health Survey data. Stratification and multistage random sampling method get 18,061 female workers as respondents. The final stage was done using binary logistic regression. The results found that there was no difference between primary education female workers and no education female workers at the risk of giving birth to LBW babies. Secondary education female workers have a 0.561 times chance compared to no education female workers to give birth to LBW babies. Meanwhile, higher education female workers have a possibility of 0.414 times compared to no education female workers to give birth to LBW babies. Apart from the education level, the results of the analysis also found two other variables as predictors of LBW among female workers, namely wealth status and ANCvisits. It was concluded that the education level is a predictor of LBW among female workers in Indonesia. The higher the education level, the lower the possibility of female workers to have LBW babies in Indonesia.